2020
DOI: 10.12688/gatesopenres.13161.1
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for PMA-Ethiopia: A new data source for cross-sectional and longitudinal data of reproductive, maternal, and newborn health

Abstract: Background: Performance Monitoring for Action Ethiopia (PMA-Ethiopia) is a survey project that builds on the PMA2020 and PMA Maternal and Newborn Health projects to generate timely and actionable data on a range of reproductive, maternal, and newborn health (RMNH) indicators using a combination of cross-sectional and longitudinal data collection.  Objectives: This manuscript 1) describes the protocol for PMA- Ethiopia, and 2) describes the measures included in PMA Ethiopia and research areas that may be of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(114 citation statements)
references
References 12 publications
0
114
0
Order By: Relevance
“…48 The incidence rate ratios (IRRs) with the corresponding 95% confidence interval were reported for each explanatory variable using a p-value less than 0.05 to declare the statistical significance. 36 The data use policy of PMA Ethiopia frankly stated datasets are anonymized (ie, no result is published in which communities or individuals can be identified) before it is made publicly available for download via the www.pmadata.org website. The PMA Ethiopia review submitted requests and granted access to indicated datasets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…48 The incidence rate ratios (IRRs) with the corresponding 95% confidence interval were reported for each explanatory variable using a p-value less than 0.05 to declare the statistical significance. 36 The data use policy of PMA Ethiopia frankly stated datasets are anonymized (ie, no result is published in which communities or individuals can be identified) before it is made publicly available for download via the www.pmadata.org website. The PMA Ethiopia review submitted requests and granted access to indicated datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PMA Ethiopia was developed to provide national estimates of key RMNH indicators to identify gaps in RMNH care services through the panel study design. 36 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A multistage stratified cluster design in which all EAs were randomly selected using probability proportional to size and all households were screened to identify any women six or more months pregnant. All consenting pregnant women were interviewed at screening, seven days, six weeks, and six months postpartum by trained enumerators using smartphones programmed with Open Data Kit (ODK) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%